Better health outcomes at lower costs: the benefits of primary care utilisation for chronic disease management in remote Indigenous communities in Australia’s Northern Territory - Zhao, Yuejen (BMC Health Serv Res, 2014)
BACKGROUND: Indigenous residents living in remote communities in Australia’s Northern Territory experience higher rates of preventable chronic disease and have poorer access to appropriate health services compared to other Australians. This study compared health outcomes and costs at different levels of primary care utilisation to determine if primary care represents an efficient use of resources for Indigenous patients with common chronic diseases namely hypertension, diabetes, ischaemic heart disease, chronic obstructive pulmonary disease and renal disease. METHODS: This was an historical cohort study involving a total of 14,184 Indigenous residents, aged 15 years and over, who lived in remote communities and used a remote clinic or public hospital from 2002 to 2011. Individual level demographic and clinical data were drawn from primary care and hospital care information systems using a unique patient identifier. A propensity score was used to improve comparability between high, medium and low primary care utilisation groups. Incremental cost-effectiveness ratios and acceptability curves were used to analyse four health outcome measures: total and, avoidable hospital admissions, deaths and years of life lost. RESULTS: Compared to the low utilisation group, medium and high levels of primary care utilisation were associated with decreases in total and avoidable hospitalisations, deaths and years of life lost. Higher levels of primary care utilisation for renal disease reduced avoidable hospitalisations by 82-85%, deaths 72-75%, and years of life lost 78-81%. For patients with ischaemic heart disease, the reduction in avoidable hospitalisations was 63-78%, deaths 63-66% and years of life lost 69-73%. In terms of cost-effectiveness, primary care for renal disease and diabetes ranked as more cost-effective, followed by hypertension and ischaemic heart disease. Primary care for chronic obstructive pulmonary disease was the least cost-effective of the five conditions. CONCLUSION: Primary care in remote Indigenous communities was shown to be associated with cost-savings to public hospitals and health benefits to individual patients. Investing $1 in primary care in remote Indigenous communities could save $3.95-$11.75 in hospital costs, in addition to health benefits for individual patients. These findings may have wider applicability in strengthening primary care in the face of high chronic disease prevalence globally.